The Type of Childcare for Working Mothers in Indonesia - Sri Tatminingsih (Jurnal Pendidikan Usia Dini, 2022)
One of the problems faced by working mothers is caring for children, especially children who are still at an early age. This is because their workplace does not allow them to bring small children or does not provide daycare. This study aims to find out the types of child care that working mothers in Indonesia choose and their considerations in choosing that type. This research method uses a mixed-method design by combining two types of quantitative and qualitative data. Data collection was carried out through surveys with questionnaire instruments and interviews with working mothers. The number of respondents surveyed was 500 working mothers and 100 of them were interviewed. Interviews were conducted in person or via telephone and video calls using the Zoom meeting and WhatsApp applications. The study was conducted in 2020 and 2021. The results of the study found that five types of child care were selected with the main considerations being the child’s development, the competence and personality of the caregivers, the conditions of the living area, and considerations of cost. Keywords: early childhood, working mothers, types of care References: Alsheikh, N., Parameswaran, G., & Elhoweris, H. (2010). Parenting style, self-esteem, and student performance in the United Arab Emirates. Current Issues in Education, 13(1), 1–26. Amalia, R. P., Abidin, F. A., & Lubis, F. Y. (2022). Parenting Stress, Mother’s Assessment Of Covid-19, And Supportive Parenting [Stres Pengasuhan, Penilaian Ibu Terhadap Covid-19, Dan Pengasuhan Suportif ]. Jurnal Ilmu Keluarga Dan Konsumen, 15(1), 51–62. https://doi.org/10.24156/jikk.2022.15.1.51 Arabi, R., Mamat, R., Rashid, N. A., & Bakri, R. (2018). Working Mothers’ Knowledge of Exclusive Breastfeeding in Hospital Canselor Tuanku Muhriz (HCTM) (Pengetahuan Penyusuan Susu Ibu Secara Eksklusif dalam Kalangan Ibu Bekerja di Hospital Canselor Tuanku Muhriz (HCTM)). Jurnal Sains Kesihatan Malaysia, 16(1), 163–168. Creswell, J. W., & Clark, V. L. P. (2011). Designing and Conducting Mixed Methods Research. SAGE Publications. https://books.google.co.id/books?id=YcdlPWPJRBcC De Almeida, L. S. (2012). Working mothers and their multivoiced self. Revista Colombiana de Psicologia, 21(2), 313–322. Dey, S., Patra, A., Giri, D., Sharma, J., & Anna, L. (2021). The effectiveness of Parental Intervention in Teaching Emotional Intelligence to Their Adole scent Children. International Education & Research Journal [IERJ], 7(December), 9–12. Dhingra, V., & Keswani, S. (2019). Impact of Working and Non—Working Mothers on Development of their Children in Madhya Pradesh. International Journal of Research in Advent Technology, 7(3), 1369–1375. https://doi.org/10.32622/ijrat.732019104 Friska Realita. (2019). Relationship between Knowledge Level of Health Workers and Government Regulation No. 33 of 2012 concerning Exclusive Breastfeeding [Hubungan Tingkat Pengetahuan Tenaga Kesehatan terhadap Peraturan Pemerintah No.33 Tahun 2012 Tentang Pemberian ASI Ekslusif]. Jurnal Kebidanan, 8(33), 43–49. https://doi.org/10.26714/jk.8.1.2019.43-49 Hakiki, G., & Idha, S. (2021). Women and Men in Indonesia 2021. BPS-Statistics Indonesia, viii+39. Handayani, A., Yulianti, P. D., & M., P. D. (2019). Module Validation of Equal Roles for Men and Women to Achieve Work-Family Balance [Validasi Modul Kesetaran Peran Laki-Laki dan Perempuan untuk Mencapai Keseimbangan Kerja-Keluarga] Musãwa Jurnal Studi Gender Dan Islam, 18(2), 173. https://doi.org/10.14421/musawa.2019.1832.173-182 Hidayah, N., Tarnoto, N., & Maharani, E. A. (2019). Profile of Child Care Needs in Young Couples [Profil Kebutuhan Pengasuhan Anak pada Pasangan Muda]. Jurnal Ilmu Perilaku, 2(2), 89. https://doi.org/10.25077/jip.2.2.89-106.2018 Hurst, M., & Zambrana, R. E. (1982). Child Care and Working Mothers in Puerto Rican Families. The ANNALS of the American Academy of Political and Social Science, 461(1), 113–124. https://doi.org/10.1177/0002716282461000012 Meier, P., & Mead, L. (1978). Working Mothers. Journal of Obstetric, Gynecologic, & Neonatal Nursing, 7(3), 49–49. https://doi.org/10.1111/j.1552-6909.1978.tb00746.x Merlina, N. (2010). Parenting Patterns in the Giri Jaya Indigenous Community [Pola Pengasuhan Anak pada Komunitas Adat Giri Jaya]. Patanjala: Balai Pelestarian Sejarah Dan Nilai Tradisional Bandung, 2(2), 241–257. Montgomery, K. S. (2002a). Information for working mothers. The Journal of Perinatal Education an ASPOLamaze Publication, 11(2), 44–45. https://doi.org/10.1624/105812402X88713 Montgomery, K. S. (2002b). Resource Column: Information for Working Mothers. The Journal of Perinatal Education, 11(2), 44–45. https://doi.org/10.1891/1058-1243.11.2.44 Nilam Sari, P. (2017). Increasing the Success of the Exclusive Breastfeeding Program for Working Mothers as an Effort to Achieve the MDGs [Meningkatkan Kesuksesan Program ASI Ekslusif pada Ibu Bekerja sebagai Upaya Pencapaian MDGs]. Jurnal Kesehatan Masyarakat Andalas, 9(2), 93. https://doi.org/10.24893/jkma.9.2.93-97.2015 Odenweller, K. G., & Rittenour, C. E. (2017). Stereotypes of Stay-at-Home and Working Mothers. Southern Communication Journal, 82(2), 57–72. https://doi.org/10.1080/1041794X.2017.1287214 R, R., & Chacko, E. (2019). Effectiveness of Day Care center son working Mothers. Center for Management Studies, Jain University,. Retnaningsih, W., & Setiyawati, D. (2019). Validation of the Positive Discipline Training Module to Improve Parenting Practices in Mothers of Preschool Children [Validasi Modul Pelatihan Disiplin Positif untuk Meningkatkan Praktik Pengasuhan pada Ibu Anak Prasekolah]. Gadjah Mada Journal of Professional Psychology (GamaJPP), 5(2), 158. https://doi.org/10.22146/gamajpp.50373 Rimba Eka Handini, Haryoko, S. F., & Yulianto, A. (2017). Relationship between Work-Family Conflict and Work Engagement [Hubungan antara Work-Family Conflict dan Keterikatan Kerja pada Ibu Bekerja]. Jurnal NOETIC Psychology, 4(July-Deesember), 169–180. Salum, E. D. O., Lima, J. C., Marcacine, P. R., Walsh, H. P., & Walsh, I. A. P. de. (2020). Epidemiological profile of working mothers. Revista Família, Ciclos de Vida e Saúde No Contexto Social, 8(2), 200. https://doi.org/10.18554/refacs.v8i2.4525 Saraswati, W., & Febriani, Z. (2018). Relationship between Mindful Parenting and Parenting Style in Mothers with Children Aged 3-6 Years. [Hubungan antara Mindful Parenting dengan Gaya Pengasuhan pada Ibu yang Memiliki Anak Usia 3-6 Tahun]. Journal Psikogenesis, 6(2), 214–222. https://doi.org/10.24854/jps.v6i2.704 Shao, M., He, W., Zhao, L., & Su, Y. S. (2022). The Influence of Parental Involvement on Parent Satisfaction: The Moderating Effect of Parental Educational Level and the Number of Children. Frontiers in Psychology, 12(January). https://doi.org/10.3389/fpsyg.2021.752802 Sim, W. H., Jorm, A. F., & Yap, M. B. H. (2022). The Role of Parent Engagement in a Web-Based Preventive Parenting Intervention for Child Mental Health in Predicting Parenting, Parent and Child Outcomes. International Journal of Environmental Research and Public Health, 19(4). https://doi.org/10.3390/ijerph19042191 Widyastuti, S. B., Soedjatmiko, & Firmansyah, A. (2011). Growth and development profile of children at two-day care centers in Jakarta. Paediatrica Indonesiana, 45(11–12), 275–279. https://doi.org/10.14238/pi Xia, X. (2022). Family Income, Parental Education and Chinese Preschoolers’ Cognitive School Readiness: Authoritative Parenting and Parental Involvement as Chain Mediators. Frontiers in Psychology, 13(March). https://doi.org/10.3389/fpsyg.2022.745093 Ye, P., Ju, J., Zheng, K., Dang, J., & Bian, Y. (2022). Psychometric Evaluation of the Parental Reflective Functioning Questionnaire in Chinese Parents. Frontiers in Psychology, 13(January). https://doi.org/10.3389/fpsyg.2022.745184 Zimmermann, G., Antonietti, J.-P., Mageau, G., Mouton, B., & Van Petegem, S. (2022). Parents’ Storm and Stress Beliefs about Adolescence: Relations with Parental Overprotection and Parental Burnout. Swiss Psychology Open, 2(1). https://doi.org/10.5334/spo.31